XXVI Galyna Puchkovska International School-Seminar “Spectroscopy of Molecules and Crystals” - Doroshenko, Iryna; Berezovska, Nataliya; Gavrilko, Tetiana (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2024)
This special issue of Low Temperature Physics contains selected contributions presented at XXVIth Galyna Puchkovska International School-Seminar “Spectroscopy of Molecules and Crystals” (ISSSMC-2024) organized by the Institute of Physics of the National Academy of Sciences of Ukraine and Taras Shevchenko National University of Kyiv under the auspice of the National Academy of Sciences of Ukraine and Ukrainian Physical Society. It comprises 19 articles that cover a broad range of spectroscopic studies on both organic and inorganic materials, hybrid organic–inorganic nanomaterials, and biological systems, ranging from fundamental investigation of their molecular properties to practical applications in various fields, including health and environmental problems. The ISSSMC-2024 was organized in honor of the late Professor Galyna Puchkovska (22.06.1934–29.09.2010), an outstanding Ukrainian scientist, a heartfelt friend, and well-respected member of the spectroscopy community, who was the founder and the soul of this conference. Her influence on the life of her friends and colleagues can hardly be overestimated. She always will be in our hearts and never will be forgotten.